Implementasi Kebijakan Pembatasan Sosial Berskala Besar dalam Penanggulangan COVID-19 di Pekanbaru - Wan Asrida; Auradian Marta; Wazni Wazni (Nakhoda: Jurnal Ilmu Pemerintahan, 2022)
This study departs from empirical facts which show that the outbreak of COVID-19 transmission in Pekanbaru City has started to worry, including the highest category in Riau Province. Policies for handling COVID-19 have also been made to anticipate transmission of the virus through Large-Scale Social Restrictions (PSBB). Thus, this study is directed to answer a fundamental question, namely how is the implementation of large-scale social restriction policies in tackling COVID-19 in Pekanbaru. To answer this question, the theory of policy implementation put forward by Van Meter & Van Horn is used. This study uses a qualitative research method in which data collection is carried out by in-depth interviews and document searches. The findings of this study indicate that the implementation of the PSBB policy has not been able to reduce the transmission of the COVID-19 outbreak in Pekanbaru. Even though, in substance, the PSBB policy has regulated in detail regarding the handling of COVID-19 and budgetary resources as well as multi-actor involvement with communication and coordination in policy content. However, economic environmental factors have contributed to the failure to implement the COVID-19 countermeasures policy in Pekanbaru.